The Philosophy of Multicultural Education as a Foundation for Strengthening the Literacy and Identity of Banda Neira Children - Yuliati, Ni Komang Dwi Eka; Tika, I Nyoman; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Banda Neira has a central role in the birth of Indonesia as a country with the motto of Bhineka Tunggal ika. Banda Neira is often positioned as the "zero point" of colonialism as well as a laboratory of Indonesian multiculturalism. With a history of genocide, forced migration, and complex new identity formation, on the other hand Banda shows how to validate trauma while celebrating resilience and hope. In the context of multicultural education, in Banda Neira we can learn about diversity but also respects unity. Glorifying the heritage of history, as well as moving forward in a coherent education according to the uncertain demands of global education. In this context, early grade reading literacy can be used as a crucial space to reconstruct historical memory, manage trauma, resilience, and foster pride in the identity of Banda children who live in a plural reality. This paper examines multicultural education in Banda Neira from the perspective of educational philosophy, especially the ideas of Dewey, Piaget, Vygotsky, Bandura, and Freire, and relates it to the practice of early grade reading literacy and the gap between conceptual- ideals and realities in the field. In particular, the analysis is directed at the phenomenon of Banda children who are familiar with the tagline "don't die before going to Banda Neira", but do not necessarily internalize the philosophical and historical meaning behind the pride. With a qualitative-reflective approach based on literature review, this article shows that Freire's dialogical and critical multicultural education, starting with early grade reading literacy, has the potential to transform popular slogans into historical awareness, resilient collective identities, and liberating pedagogical praxis.